2020
DOI: 10.20396/bjos.v19i0.8656652
|View full text |Cite
|
Sign up to set email alerts
|

Removable prostheses improve OHRQL and satisfaction of elderly people with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease that affects joint tissues and causes severe physical and functional impairments on quality of life due to muscular and articular pain. The involvement of temporomandibular joint in RA interferes with mouth opening and masticatory process. However, no studies addressed the impact of RA on oral health-related quality of life (OHRQoL) and satisfaction with prostheses use in elderly people. Aim: This study assessed the impact of oral rehabilitation with conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Our results agree with Lemos et al 22 (2013), as their findings suggested that being completely edentulous or wearing non-fixed complete dentures, and regular, poor or extremely bad oral health were important features for negative self-perception of oral health with impact on the volunteer's quality of life 22 . Moreover, the oral health appreciation can be affected by general conditions such as rheumatoid arthritis 23 or local commodities, such as stomatitis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with Lemos et al 22 (2013), as their findings suggested that being completely edentulous or wearing non-fixed complete dentures, and regular, poor or extremely bad oral health were important features for negative self-perception of oral health with impact on the volunteer's quality of life 22 . Moreover, the oral health appreciation can be affected by general conditions such as rheumatoid arthritis 23 or local commodities, such as stomatitis 24 .…”
Section: Discussionmentioning
confidence: 99%